A biomass-derived nitrogen-doped porous carbon for high-energy supercapacitor. (December 2018) - Zhu, Youyu; Chen, Mingming; zhang, Yang; Zhao, Wenxuan; Wang, Chengyang
Abstract: In present work, a novel strategy combining the nitrogen-functionalization and pore structure controlling was developed to prepare nitrogen-doped hierarchical porous carbons (NHPCs) from a bio-decomposited product. This strategy was realized by introducing nitrogen species into the carbon precursor to afford CN forms, which would react with the K-species and thus enhance the carbon etching to improve the pore structure development. The final NHPCs obtained by this strategy not only have a high nitrogen content of 5 at %, but also deliver specific surface area up to 3142 m 2 g −1 and total pore volume close to 2.6 m 3 g −1 . Benefited from the chemical composition and improved pore structure, the NHPCs electrodes exhibit an impressive capacitive performance in ionic liquid electrolyte with high specific capacity (209 F g −1 at 0.05 A g −1 and 148 F g −1 at 20 A g −1 ), enhanced energy density (up to 88 W h kg −1 ) and superior cyclic stability (a capacitance loss of 9% after 10000 cycles). The desirable electrochemical performance combined with the green and low-cost precursor and the simple and scalable synthesis route make the NHPCs sample a promising candidate for high-energy supercapacitor. Graphical abstract: Image 1